Perceraian dan Penguatan Hak-hak Perempuan: Reformasi Hukum Keluarga di Mesir, Indonesia dan Pakistan - Rizki Amar; Jamilatuz Zahrah; Lisa Hertiana (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
One of the motives for family law reform in the Islamic world is to strengthen the rights of women who tend to be discriminated against and subordinated. Egypt introduced its first family law reform by passing Laws No.25 of 1920 and 1929. Pakistan, through the Muslim Family Law Ordinance of 1961, regulates the issue of divorce and guarantees women's rights in it. Meanwhile, in Indonesia the rules regarding divorce are contained in the 1974 Marriage Law and the Compilation of Islamic Law. This article reviews the development of family law in Egypt, Indonesia and Pakistan, highlights the approaches and methods used in reform, and explores the extent to which family law reforms strengthen women's rights, especially in the field of divorce. The method used in this article is a literature study, by collecting secondary data from relevant literature and then describing it. The findings of the study show that family law reforms in Egypt, Indonesia and Pakistan use intra-doctrinal reform and extra-doctrinal reform approaches. Substantively, the reforms have strengthened women's rights in at least two aspects: first, the limitation of the husband's right to divorce, and second, the expansion of women's access to apply for divorce. Although subtantively the law has strengthened women's rights, in practice divorce and its settlement in the three countries still leave problems and sometimes harm women.